EFEKTIVITAS BANTUAN LANGSUNG TUNAI DARI PEMERINTAH PROVINSI RIAU BAGI MASYARAKAT TERKENA DAMPAK COVID-19 DI KELURAHAN TANGKERANG LABUAI KECAMATAN BUKIT RAYA KOTA PEKANBARU TAHUN 2020 - Christy Natalica Natalica T; Sofyan Hadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The implementation of the Riau Provincial Government's Direct Cash Assistance (BLT) program in Pekanbaru City caused turmoil in the community, especially in Tangkerang Labuai Village, Bukit Raya District, in terms of disbursing BLT related to differences in KK/KTP numbers registered with channeling banks and the occurrence of BLT deductions at one of the banks. distribution bank. This indicates that the Pekanbaru City Government and stakeholders have not been effective in distributing the Riau Provincial Government BLT.This study aims to describe how the effectiveness of the Riau Provincial Government Direct Cash Assistance (BLT) in supporting people's purchasing power in the midst of the economic downturn due to COVID-19. This study uses a qualitative approach with a descriptive method. In collecting data, the author uses interview and documentation techniques.The results of this study are that it can be seen that the effectiveness of the implementation of the Riau Provincial Government's BLT program has not been maximized in its implementation. This is due to several things, namely the absence of continuous socialization and only carried out by the village government regarding the Riau Provincial Government BLT. The initial data collection carried out for KPM is not well targeted and uneven, so there are still KPM members who do not meet the target criteria that have been set. Many KPMs have difficulty in taking BLT funds, lack of understanding of KPMs regarding complaints regarding problems related to taking BLT.Keyword : Program Effectiveness, Riau Provincial Government Cash Direct Aid